How should news shocks be specified under rational expectations? - Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2017)
A number of studies have found that news shocks account for a large part of the aggregate fluctuations of the main macroeconomic variables.We show that when taking rational expectations into consideration there is a limit on the size of the variance of the news shocks,which has not been considered in the literature.We offer an explanation to why this restriction should be imposed and show,with an empirical example from a recent paper,that if you do impose the rational expectations restriction the importance of the news is drastically reduced.
Keywords: E2; E3; 330; News shocks; DSGE; Rational Expectations